Figurative Language Applied In “The Show” Album By Niall Horan - Dian Eklesia (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2023)
Songs and language are inseparable companions in the world of music. Language is the framework on which songs are constructed, allowing songwriters and performers to engage audiences intellectually and emotionally by sharing their thoughts, feelings, and tales in songs. Figurative language and songs share a deep and symbiotic relationship. In order to give their lyrics emotion, depth, and inventiveness, lyricists employ a variety of figurative language techniques. This helps listeners engage with the music on a visceral and emotional level. Figurative language is an effective tool for turning lyrics into an engaging and memorable storytelling experience. The objective is to find out the figurative language applied in ‘The Show’ Album by Niall Horan. The method used for this study is descriptive qualitative method and used Kennedy and Gioia (1995) figurative languages as the theory. Various sources such as undergraduate thesis, articles, books, and internet sources are used to provide further information. The findings of this article are seven songs on the album that contain figurative language. The result is that four data in simile is found, one data in metaphor, five data in hyperbole, four data in personification, three in metonymy, and one in synecdoche.